2008
DOI: 10.3200/socp.148.6.745-764
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Familial Functioning of Children From Polygynous and Monogamous Families

Abstract: A sample of 352 Bedouin Arab children--174 from monogamous and 178 from polygynous families--participated in this study. The authors used self-reported standardized measures to assess the participants' level of self-esteem, mental health, social functioning, father-child relationships, mother-child relationships, and family functioning. The findings revealed that children from polygynous families reported more mental health and social difficulties as well as poorer school achievement and poorer relationships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
2
39
1
Order By: Relevance
“…Likewise, as indicated in Tables 2 and 3, many of the mental health symptoms were more common for polygamous women; particularly noteworthy were somatization, obsessive compulsive, interpersonal sensitivity, depression, hostility psychoticism and the GSI. Findings from the current study regarding polygamy among Syrians' women is consistent with previous studies conducted in UAE, Kuwait, Egypt, Jordan, the Gaza Strip, Arabs in Israel, Palestine and Turkey which point out that the wives in polygamous marriages have reportedly more psychosocial, familial and economic problems compared to their counterparts from monogamous families [4,14,20,28] . A recent Turkish study found out that the participants from polygamous families, especially senior wives, reported more psychological distress [19] .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Likewise, as indicated in Tables 2 and 3, many of the mental health symptoms were more common for polygamous women; particularly noteworthy were somatization, obsessive compulsive, interpersonal sensitivity, depression, hostility psychoticism and the GSI. Findings from the current study regarding polygamy among Syrians' women is consistent with previous studies conducted in UAE, Kuwait, Egypt, Jordan, the Gaza Strip, Arabs in Israel, Palestine and Turkey which point out that the wives in polygamous marriages have reportedly more psychosocial, familial and economic problems compared to their counterparts from monogamous families [4,14,20,28] . A recent Turkish study found out that the participants from polygamous families, especially senior wives, reported more psychological distress [19] .…”
Section: Discussionsupporting
confidence: 89%
“…Families living together in crammed and overcrowded conditions, can create an environment that aggravates stress and conflict between co-wives [34] . Previous research reveals significant implications regarding children's lower academic achievements, and men's psychological problems, amongst polygamous marriages [20] . The practice has implications for entire familial structures, and for current and future families and communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been made on Arab population in Israel (Al-Krenawi, Graham, & Al-Krenawi, 1997;Al-Krenawi, Graham, & Slonim-Nevo, 2002;Al-Krenawi & Lightman, 2000;Al-Krenawi & Slonim-Nevo, 2008;Elbedour, et al, 2000;Elbedour, Onwuegbuzie, & Alatamin, 2003). One study has been made in South Africa (Cherian, 1990).…”
Section: Impact Of Polygamy On Childrenmentioning
confidence: 99%
“…It can be defined as any form of marriage in which a person has more than one spouse (1). Several forms of polygamy have been described.…”
mentioning
confidence: 99%